“Breathing” in Adsorbate-Responsive Metal Tetraphosphonate Hybrid Materials - Pérez-Colodrero, Rosario Mercedes; Cabeza-Díaz, Aurelio; Olivera-Pastor, Pascual; Infantes-Molina, Antonia; Barouda, Eleni; Demadis, Konstantinos D.; García-Aranda, Miguel Ángel (Wiley-VCH Verlag GmbH&Co. KGaA, Weinheim, 2009)
The structures of various layered calcium tetraphosphonates (CaH6DTMP; H8DTMP=hexamethyl- tetrakis(methylenephosphonic acid)), have been determined. Starting from CaH6DTMP·2H2O, thermal treatment and subsequent exposure to NH3 and/or H2O vapors led to four new compounds that showed high storage capacity of guest species between the layers (up to ten H2O/NH3 molecules) and a maximum volume increase of 55%. The basic building block for these phosphonates consists of an eight-membered ring chelating Ca2+ through two phoshonate groups, and the organic ligand is located within the layers, which are held together by hydrogen bonds. The structural analysis revealed that the uptake/removal of guest species (H2O and NH3) induces significant changes in the framework not only by changing the interlayer distances but also through important conformational changes of the organic ligand. An anisotropic breathing motion could be quantified by the changes of the unit-cell dimensions and ligand arrangements in four crystalline derivatives. Complete characterization revealed the existence of interconversion reactions between the different phases upon gas uptake and release. The observed behavior represents, to the best of our knowledge, the first example of a breathing-like mechanism in metal phosphonates that possess a 2D topology.
Keywords: Química inorgánica; X-ray diffraction; Host–guest systems; Hydrogen bonds; Hybrid materials; Tetraphosphonates